Review article of Waltraud Paul’s New Perspectives on Chinese Syntax (2015) - Li, Yen-hui Audrey (Glossa (London), 2016)
Taking Paul (2015) as a starting point, this article discusses different approaches concerning the contribution made by Chinese to general syntactic theory and typology. It demonstrates that the solution of basic questions such as the precise inventory of lexical categories can have far-reaching consequences for more general issues such as case theory, linearization, head parameter and the status of typological universals.